Pengembangan Pendekatan Audit Teknologi untuk Optimalisasi Pengelolaan IPLT dengan Teknologi Pengolahan Semi-mekanis (Studi Kasus: IPLT Kalimulya Depok) - Anggita Laksmi Prameswari; Dyah Wulandari Putri (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The 2030 Sustainable Development Goals (SDGs), based on human rights and equality, urge developing countries, including Indonesia, to accelerate development efforts, particularly in the area of sanitation. In line with the SDGs, Indonesia has set a national medium-term development plan (RPJMN) for 2020-2024 that aims to achieve 90% access to adequate sanitation, with 15% designated as safe sanitation and 0% open defecation. The safe sanitation targets are driving the development of septage treatment plants (IPLT) in various cities and districts in Indonesia. Indonesian IPLTs are transitioning from traditional to semi-mechanical or fully mechanical systems. The Kalimulya IPLT uses a semi-mechanical approach, combining conventional wastewater treatment with mechanical sludge treatment. This study evaluates the IPLT Kalimulya using a technology audit approach based on the UNESCAP (1989) methodology to identify factors affecting the optimisation of IPLT management. The assessment of technoware, humanware, infoware and orgaware revealed an overall Technology Capability Classification (TCC) score of 0.55 for IPLT Kalimulya, indicating a 'good' category with semi-modern technology. The infoware component achieved the highest score, reflecting strong performance, while the humanware and technoware components were rated at a standard level.